Accounting Learning Gaps of K-12 Accountancy, Business, and Management (ABM) Graduates: Basis for Remediation Program for BSA Accountancy Program of Sorsogon State University (SorSu) - Bongalonta, Michael B.; Bongalonta, Michelle M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study was conducted to identify the accounting learning gaps of K-12 ABM graduates enrolled in the Sorsogon State University (SorSU) BS in Accountancy program in the Academic Year 2021-2022. This study used mixed design to quantitatively determine the accounting learning gaps of K-12 ABM Graduates explore those issues concerning the causes of accounting learning gaps encountered by the respondents. Results revealed that student-respondents were found to have weakness or very little accounting knowledge and skills were attributed to some factors such Limited Accounting Background and Proper Preparation, Lack of Calculation Skills, Non-integration of Accounting Lessons into Real-Life Context, Limited Physical and Human Resources are Available for the Implementation of the Accountancy, Business and Management (ABM) Track under the K-12 System and Students Study Habits and Approaches. The Proposed Accounting crash Corse was deemed necessary to address the identified learning gaps of ABM Graduates.